Pesantren Strategy In Preventing Acts Of Bullying - Ummatus Sakinah; Muhamad Arif (Journal of Social Science and Economics, 2022)
The number of educational institutions in Indonesia makes parents more flexible in providing the best education for their children. In Indonesia, there is the oldest educational institution, namely pesantren. As the oldest institution in Indonesia, Islamic boarding schools have several differences from other educational institutions. Islamic boarding schools are also known as institutions that prioritize discipline and dedication to their teachers. Living in a boarding school with a variety of different characters is very prone to bullying. Bullying is the act of using power to hurt a person or group of people verbally, physically or psychologically so that the victim feels pressured, traumatized and helpless. Researchers got information that the Darul Ihsan Menganti Gresik Islamic Boarding School applied various habits to prevent acts of bullying. In order to create a boarding school that is child-friendly and cares about the welfare of its students. This made the researchers want to learn more about the strategies that have been implemented by Pondok Pesantren Darul Ihsan Menganti Gresik in preventing bullying. This research is a type of research that is qualitative in nature, namely a research that intends to understand the phenomenon of what is experienced by research subjects such as behavior, perceptions, motivations, actions, and others in a holistic manner. The results of the study revealed that Pondok Darul Ihsan had implemented several bullying prevention strategies. Among them are establishing communication, anti-bullying seminars, strengthening parents and children, special counseling and religious activities.